Identification of spermatogonial stem cell-like cell differentiation in vitro from azoospermia patient using modified human embryonic stem cell (HESC) media - Abdul Wahab, Azantee Yazmie; Md Isa, Muhammad Lokman; Ramli, Roszaman (OMICS International, 2015)
Background:Spermatogenesis is a process where proliferation and differentiation of spermatogonial stem cell (SSC) into haploid sperm cells in the testis. Azoospermia patients have impaired spermatogenesis where they have difficulty to get normal sperm. The purpose of this study is to proliferate and differentiate SSC-like cell in in vitro culture from azoospermia patient samples and to determine the pattern of gene expressions involved. Methods and Results: Testicular biopsy tissue obtained from obstructive azoospermia (OA) and non-obstructive azoospermia (NOA) patients were dissociated and cultured in different human embryonic stem cell (HESC) media added with specific growth factors and reproductive hormones according to the day of culture using 24 well plate dishes. SSC-like cell colonies were formed after 5 weeks of culture. Gene expression analyses were done on day 49 and day 90 using quantitative reverse transcription polymerase chain reaction (q-RT PCR). OCT4 was detected in NOA patient and ITGB1 was identified in OA patient for 49 days of culture. Gene expression for all stages of spermatogenic cells in day 90 were mostly detected in OA patient; ITGB1, SCP3, H2B and TNP1. However, gene TNP1 was only expressed in NOA patient shown spermatid formation stage. Conclusions: Our result shown that there is a potential to develop sperm in vitro culture from testis biopsy of azoospermic patients for further clinical application